PENGARUH UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI - Inge Lengga Sari Munthe (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2019)
ABSTRACT This research aims to analyze the effect company size to earning management with capital structure as moderating variable in sub sector textile and garment in Bursa Efek Indonesia from 2015 until 2018.. It uses purposive sampling to take sample. There are 16 companies as samples. Reseach method with statistic test where use moderating regression analysis. The results are company size and capital structure have effect on earning management for simltaneously and partial respectively. Capital structure also strength the effect beween company size with earning management.